Why did you do that? Differential types of aggression in offline and in cyberbullying. (March 2022) - Graf, Daniel; Yanagida, Takuya; Runions, Kevin; Spiel, Christiane
Abstract: Traditional conceptualizations of aggression distinguish between reactive (e.g., rage) and proactive (e.g., reward) functions of aggression. However, critiques of this dichotomy have pointed out these models conflate motivational valence and self-control. Addressing this weakness, recent conceptualizations consider four types of aggression: rage, revenge, reward, and recreation aggression. The goal of the present study was to investigate contextual differences in the distribution of the four types of aggression as drivers of offline and cyberbullying among self-reported aggressors. A total of 839 participants (♀ = 70.26%; Mage  = 23.41, SD = 9.21) answered questionnaires regarding their offline and cyberbullying behavior. If participants indicated that they had engaged in bullying behavior within the last two months, they had to specify why they had engaged in this behavior. Controlling for gender, age and the level of offline and cyberbullying, mixed effects logistic regression analyses revealed that cyberbullying was more likely to result from recreation aggression than offline bullying, whereas offline bullying was more likely to result from reward, rage, and revenge aggression than cyberbullying. In summary, the present study uncovers differences in the underlying aggression between offline and cyberbullying, thus providing information for environment-specific prevention and intervention programs. Highlights: A fine-grained typology of aggression was used to compare the underlying motives in offline and cyberbullying. Recreation motives are more likely in cyberbullying compared to offline bullying. Rage, revenge and reward motives are more likely in offline bullying compared to cyberbullying.